2021
DOI: 10.1186/s13063-021-05039-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical acupoint stimulation for high-normal blood pressure: study protocol for a randomized controlled pilot trial

Abstract: Background High-normal blood pressure (BP) is associated with increased all-cause, cardiovascular mortality and frequently progresses to hypertension. Transcutaneous electrical acupoint stimulation (TEAS) might be a non-pharmaceutical therapy option to control BP. This trial aims to determine the effectiveness and safety of TEAS combined with lifestyle modification for high-normal BP. Methods/design This prospective, randomized, and parallel clinic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It plays an important role in the treatment of neurological diseases by regulating the related pathways to repair the damage. It has a good effect on the complications of neuropathic pain, neurogenic bladder, and digestive tract disorders after SCI [5][6][7]. Basic studies have found that EA stimulation of Dazhui and Mingmen acupoints can inhibit the expression of G1uR1 in SCI rats, reduce the excitotoxicity of glutamate, and promote the recovery of neuronal and hindlimb motor functions [8].…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in the treatment of neurological diseases by regulating the related pathways to repair the damage. It has a good effect on the complications of neuropathic pain, neurogenic bladder, and digestive tract disorders after SCI [5][6][7]. Basic studies have found that EA stimulation of Dazhui and Mingmen acupoints can inhibit the expression of G1uR1 in SCI rats, reduce the excitotoxicity of glutamate, and promote the recovery of neuronal and hindlimb motor functions [8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that 18 sessions of electroacupuncture during a 6-weeks time period caused an 8-mmHg reduction in SBP for patients with mild hypertension, and the effect on SBP reduction lasted for another 6 week after the acupuncture treatment was terminated. 29 In this trial, we found that TEAS combined with lifestyle modification lowered the mean SBP by 5 mmHg and lowered the mean DBP by 3 mmHg. One possible reason for the discrepancies may be the differences in the therapeutic schedule.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, the study was registered in the Chinese Clinical Trial Registry (ChiCTR 1900024982) on August 6, 2019. Details of the trial's design and analysis plan have been previously published 29 …”
Section: Methodsmentioning
confidence: 99%
“…The instrument has ten levels of stimulus intensities, and patients asked to increase the stimulus intensity until local, rhythmic contractions of the muscle are obtained without producing pain. According to the previous studies,16 19 21 22 bilateral Hegu (LI4), Quchi (LI11), Zusanli (ST36) and Taichong (LR3) will be used in our trial. On the first day, the electrodes will be placed at the ipsilateral LI4 and LI11, and the appropriate stimulus intensity will last for 15 min.…”
Section: Methodsmentioning
confidence: 99%